Miracle - Cummings, Ray, 1887-1957; Musacchia, John B., 1916-2004 (Salt Lake City, UT : Project Gutenberg, 2022)
"Miracle" by Ray Cummings is a science fiction novel written in the early 20th century. The book explores themes of time travel, fate, and destiny as it tells the story of Alan Dane, who embarks on a journey through time to rescue two individuals in the past, thus influencing the course of history. The narrative follows Alan Dane as he inherits his grandfather's ambition to develop a time-traveling device. After successfully activating the machine, Alan travels back to the year 1650, where he meets Peter Van Saant and Greta Dykeman, who find themselves threatened by an attack from Native Americans. Alan intervenes to save them, using his knowledge of their impending danger and the miraculous nature of his appearance to frighten off their attackers. Following his heroic act, Alan learns the profound historical significance of his journey, realizing that his actions were essential in ensuring the continuation of his own lineage. The story culminates in Alan$1 (Bs reflection on destiny and the interconnectedness of life across time, underscoring the idea that the past, present, and future are intricately linked. (This is an automatically generated summary.)s
Release date is 2022-10-13
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Time travel -- Fiction